Acceptance of the coronavirus disease- 2019 vaccine among medical students in Uganda - Kanyike, Andrew Marvin; Olum, Ronald; Kajjimu, Jonathan; Ojilong, Daniel; Madut Akech, Gabriel; Nassozi, Dianah Rhoda; Agira, Drake; Kisaakye Wamala, Nicholas; Asiimwe, Asaph; Matovu, Dissan; Nakimuli, Ann Babra; Lyavala, Musilim; et al. (Tropical medicine and health, 2021)
COVID-19 is still a major global threat for which vaccination remains the ultimate solution. Uganda reported 40,751 cases and 335 deaths as of 9 April 2021 and started its vaccination program among priority groups like health workers, teachers, those with chronic diseases among others in early March 2021. Unanimous uptake of the COVID-19 vaccine is required to subsequently avert its spread; therefore, we assessed COVID-19 vaccine acceptability, hesitancy, and associated factors among medical students in Uganda. Methods: This study employed an online descriptive cross-sectional survey among medical students across 10 medical schools in Uganda. A structured questionnaire via Google Form was conveniently sent to eligible participants via WhatsApp. Each medical school had a coordinator who consistently shared the data tool in the WhatsApp groups. Chi-square or Fisher’s exact test, and logistic regression were used to assess the association between vaccine acceptability with demographics, COVID-19 risk perception, and vaccine hesitancy. Results: We surveyed 600 medical students, 377 (62.8%) were male. COVID-19 vaccine acceptability was 37.3% and vaccine hesitancy 30.7%. Factors associated with vaccine acceptability were being male (adjusted odds ratio (aOR) = 1.9, 95% CI 1.3–2.9, p=0.001) and being single (aOR= 2.1, 95% CI 1.1–3.9, p=0.022). Very high (aOR= 3.5, 95% CI 1.7– 6.9, p<0.001) or moderate (aOR =2.2, 95% CI 1.2–4.1, p=0.008) perceived risk of getting COVID-19 in the future, receiving any vaccine in the past 5 years (aOR= 1.6, 95% CI 1.1–2.5, p=0.017), and COVID-19 vaccine hesitancy (aOR 0.6, 95% CI 0.4–0.9, p=0.036). Conclusions: This study revealed low levels of acceptance towards the COVID-19 vaccine among medical students, low self-perceived risks of COVID-19, and many had relied on social media that provided them with negative information. This poses an evident risk on the battle towards COVID-19 in the future especially when these future health professions are expected to be influencing decisions of the general public towards the same.
Keywords: COVID-19; Vaccine acceptance; Vaccine hesitancy; Medical students